Sustainability of community-based tourism through the lens of homestays operators in rural area of Penang, Malaysia - Radieah Mohd Nor, (Penerbit Universiti Kebangsaan Malaysia, 2024)
As a form of lodging, homestays enable individuals or families to host visitors to their homes, providing a unique opportunity for personalized experiences and cultural immersion. This alternative housing option fosters a sense of community and facilitates cross-cultural interactions, both of which benefit the tourism sector. The objective of the study is to provide recommendations for improving the sustainability of Community-Based Tourism (CBT) in rural area homestays in Penang, Malaysia. The sample for this study comprises 13 homestays managed by the local homestay association. Data collection involved qualitative research instruments: focus group discussion, observation, document analysis, and semi-in-depth interviews. The findings from all instruments were analysed through content analysis using a conceptual framework. The main findings of the study suggest that homestay operators overly rely on government funding, lack good marketing strategies, and poorly manage their finances, which leads to inadequate income generation. Through this study, researchers have developed seven tourism packages and a website to aid in marketing in rural areas, thereby increasing homestay operator income in rural Penang.